Returns to food and agricultural R&D; Investments worldwide, 1958-2015 - Hurley, Terrance; Pardey, Philip G.; Rao, Xudong; Andrade, Robert Santiago (International Science & Technology Practice & Policy Center, 2016)
Zvi Griliches published the first formal economic estimate of the rates of return to food and agricultural R&D in the Journal of Political Economy more than half a century ago. Since then many economists have published a large number of similar estimates. The consensus that has emerged from this vast body of work is that these rates of return have been exceptionally high regardless of the type of research (e.g., basic or applied), research focus (e.g., maize, wheat, rice, horticultural crops, livestock, or natural resources), or who performed the research. Yet, even with such overwhelming evidence of high rates of return, growth in public R&D spending has slowed worldwide and especially in rich countries (Pardey et al. 2016). Although agricultural commodity prices have fallen from their 2010-12 peaks, there remains widespread concern about the ability of global food supplies to meet projected demand growth. Nonetheless, current trends in public R&D spending portend slower agricultural productivity growth that is particularly disconcerting.